Bioelectrosynthesis - Harnisch, Falk; Holtmann, Dirk (Advances in Biochemical Engineering/Biotechnology, 2019)
This volume discusses both the latest experimental research in bioelectrosynthesis and current applications. Beginning with an introduction into the "electrification of biotechnology" as well as the underlying fundamentals, the volume then discusses a wide range of topics based on the interfacing of biotechnological and electrochemical reaction steps. It includes contributions on the different aspects of bioelectrochemical applications for synthesis purposes, i.e. the production of fine and platform chemicals based on enzymatically or microbially catalyzed reactions driven by electric energy. The volume finishes with a summary and outlook chapter which gives an overview of the current status of the field and future perspectives. Edited by experts in the field, and authored by a wide range of international researchers, this volume assesses how research from today's lab bench can be developed into industrial applications, and is of interest to researchers in academia and industry.